Perencanaan strategi bisnis rumah sakit ibu & anak pada rumah sakit ibu & anak swasta XYZ - Yuniarto, Aditya; Zulkifli, Zulkifli; Derriawan, Derriawan (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study focuses on how to plan a hospital's business strategy and use RSIA XYZ as a case study for a Class C private hospital. The purpose of this research is to prepare a business strategy plan for the next 5 years for RSIA XYZ. measure the success of the company's performance. This research is a qualitative research using a quantitative approach, with a descriptive question and answer analysis approach, about the strategic planning of the XYZ Hospital business from 2020 to 2024. The results show that the XYZ Hospital business strategy plan refers to the strategy in the analysis results that have been carried out. carried out, and choose the right strategy for XYZ Hospital to further formulate work plans and programs. Not only until the next work plan, but also key performance indicators (KPI) related to strategic targets will be prepared every year